FAMILY NEMESTRINIDAE - Kosmann, Cecília; Lamas, Carlos José Einicker (Zootaxa, 2016)
Nemestrinidae (Diptera, Nemestrinoidea) are a relatively rare group of flies, and the knowledge on the Colombian fauna is still incipient. According to the available literature, only one species is recorded to this country, Hyrmophlaeba magdalena Bernardi, 1977.